2022
DOI: 10.3390/pharmaceutics14102198
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystal Prediction of Bexarotene by Graph Convolution Network and Bioavailability Improvement

Abstract: Bexarotene (BEX) was approved by the FDA in 1999 for the treatment of cutaneous T-cell lymphoma (CTCL). The poor aqueous solubility causes the low bioavailability of the drug and thereby limits the clinical application. In this study, we developed a GCN-based deep learning model (CocrystalGCN) for in-silico screening of the cocrystals of BEX. The results show that our model obtained high performance relative to baseline models. The top 30 of 109 coformer candidates were scored by CocrystalGCN and then validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In the experiment finding the suitable architecture for compelling results, on trials, we tried various number convolution layers and ultimately found out that two convolution layers were promising in terms of accuracy, sensitivity, specificity, and MCC compared to the other architectures as shown in Table 3. This architecture seems to have performed better in various fields specifically cocrystal engineering, drug and protein interactions predictions 12,48,51,53 . It was observed that in Table 3 our GNN models with few layers (i.e., two layers) gave the best performance and did not improve the predictive performance and tended to perform increasingly worse on classifying graph nodes as the model gets deeper (i.e., piled up many layers and add non-linearity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experiment finding the suitable architecture for compelling results, on trials, we tried various number convolution layers and ultimately found out that two convolution layers were promising in terms of accuracy, sensitivity, specificity, and MCC compared to the other architectures as shown in Table 3. This architecture seems to have performed better in various fields specifically cocrystal engineering, drug and protein interactions predictions 12,48,51,53 . It was observed that in Table 3 our GNN models with few layers (i.e., two layers) gave the best performance and did not improve the predictive performance and tended to perform increasingly worse on classifying graph nodes as the model gets deeper (i.e., piled up many layers and add non-linearity).…”
Section: Discussionmentioning
confidence: 99%
“…It is paramount to develop complementary tools that can shorten the list selection of coformers by predicting which coformers are most likely to form cocrystals successfully. The experimental determination and traditional screening methods for cocrystals such as solution crystallization, liquid-assisted and dry grinding, and anti-solvent addition are tremendously time-consuming, economically expensive, and labor-intensive 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Graph convolutional network (GCN) is by far the most common machine learning algorithm used for cocrystal prediction, in which molecules are represented as a set of matrices to capture atom connectivity and features. Alternatively, various molecular descriptors have also been extracted and inputted in machine learning models such as multivariate adaptive regression splines, multivariable logistic regression, random forest (RF), artificial neural network (ANN), support vector machine, and extreme gradient boosting …”
Section: Introductionmentioning
confidence: 99%
“…The early approaches adopt either fully connected neural networks or tree-based models on molecular descriptors to predict the cocrystallization of molecule pairs [21,22,24]. More recent works introduced deep learning to the task and utilized convolutions over molecular graphs [10,23] to improve the predictive performance. Common to those models, they are trained on unbalanced datasets with folds of more API-coformer co-crystals than negative pairs, due to limited data availability, and struggle to generalize unseen data [21].…”
Section: Introductionmentioning
confidence: 99%